Metabolic signatures of GS‐CHO cell clones associated with butyrate treatment and culture phase transition. Issue 12 (7th July 2013) - Carinhas, Nuno; Duarte, Tiago M.; Barreiro, Laura C.; Carrondo, Manuel J. T.; Alves, Paula M.; Teixeira, Ana P.
ABSTRACT Chinese hamster ovary (CHO) cells are preferred hosts for the production of recombinant biopharmaceuticals. Efforts to optimize these bioprocesses have largely relied on empirical experience and our knowledge of cellular behavior in culture is incomplete. More recently, comprehensive investigations of metabolic network operation have started to be used to uncover traits associated with optimal growth and recombinant protein production. In this work, we used 1H‐nuclear magnetic resonance (1H‐NMR) to analyze the supernatants of glutamine‐synthetase (GS)‐CHO cell clones expressing variable amounts of an IgG4 under control and butyrate‐treated conditions. Exometabolomic data revealed accumulation of several metabolic by‐products, indicating inefficiencies at different metabolic nodes. These data were contextualized in a detailed network and the cellular fluxomes estimated through metabolic flux analysis. This approach allowed comparing metabolic activity across different clones, growth phases and culture conditions, in particular the efficiency pertaining to carbon lost to glycerol and lactate accumulation and the characteristic nitrogen metabolism involving high asparagine and serine uptake rates. Importantly, this study shows that early butyrate treatment has a marked effect on sustaining high nutrient consumption along culture time, being more pronounced during the stationary phase when extra energy generation and biosynthetic activity is fueled to increase IgG formation. Collectively, the information generated contributes to deepening our understanding of CHO cells metabolism in culture, facilitating future design of improved bioprocesses. Biotechnol. Bioeng. 2013;110: 3244–3257. © 2013 Wiley Periodicals, Inc.